2012
DOI: 10.1128/aem.02105-12
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Cryptosporidium parvum Populations Are Panmictic and Unstructured in the Upper Midwest of the United States

Abstract: e Cryptosporidium parvum is a zoonotic protozoan parasite that causes cryptosporidiosis, an infectious diarrheal disease primarily affecting humans and neonatal ruminants. Understanding the transmission dynamics of C. parvum, particularly the specific contributions of zoonotic and anthroponotic transmission, is critical to the control of this pathogen. This study used a population genetics approach to better understand the transmission of C. parvum in the Upper Midwest United States. A total of 254 C. parvum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 27 publications
4
41
0
Order By: Relevance
“…In France, the C. parvum structure ranged from basic clonality (humans) to epidemic clonality (livestock) (22), while a predominantly clonal structure was seen in Italy (39). In contrast, the C. parvum population in humans and cattle was predominantly panmictic in the upper Midwest of the United States, with limited geographic or host substructuring (40). Population analysis in the current study confirmed the evolutionary divergence of C. parvum isolates infecting domestic ruminants in our geographical area.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In France, the C. parvum structure ranged from basic clonality (humans) to epidemic clonality (livestock) (22), while a predominantly clonal structure was seen in Italy (39). In contrast, the C. parvum population in humans and cattle was predominantly panmictic in the upper Midwest of the United States, with limited geographic or host substructuring (40). Population analysis in the current study confirmed the evolutionary divergence of C. parvum isolates infecting domestic ruminants in our geographical area.…”
Section: Discussionsupporting
confidence: 64%
“…Multilocus studies of isolates from humans and livestock with VNTR markers have also identified C. parvum groups apparently restricted to humans in the United Kingdom, France, or Haiti, which supports the anthroponotic characteristics of these isolates or the occurrence of cycles that do not involve livestock (20,22,34). In contrast, no apparent host association was seen in the upper Midwest of the United States, with C. parvum being transmitted freely between cattle and humans (40). Data on the existence of specific C. parvum subpopulations within livestock species are limited.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…b Griffing et al (2011) b,c Guttman and Stavrinides (2010) b,e Grigg and Sundar (2009) c Hanage et al (2006) a,b Heitman (2006) b,c Henriques-Normark et al (2008) b,e Herges et al (2012) e Kurtenbach et al (2010) b Iwagami et al (2012) e Maiden (2006Maiden ( a , 2008 b Karunaweera et al (2008) e Martin et al (2010) e Khan et al (2011) b,e Leblois et al (2011) b Prasad Narra & Ochman (2006) a,b Lehmann et al (2004) c,e…”
Section: The Model Of Predominant Clonal Evolution and Its Last Develmentioning
confidence: 99%
“…The relative contribution of each type of population structure appears to vary between regions and hosts, and may reflect the prevailing ecological transmission dynamics (Mallon et al, 2003;Tanriverdi et al, 2008;Widmer and Sullivan, 2010;Herges et al, 2012;Widmer et al, 2015). The finding of only one C. hominis subtype by both Sanger and NGS in the kangaroo-derived DNA samples may reflect a clonal population structure operating locally in kangaroo populations from the main Sydney drinking water catchment.…”
Section: Discussionmentioning
confidence: 99%